1995
DOI: 10.1145/217278.217291
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of computer aided software engineering (CASE) technology

Abstract: This study examines the impact of various organizational and technology characteristics on the adoption of computer aided software engineering (CASE) technology. Based on research in innovation adoption and IS implementation, the study develops a research model comprised of seven factors that are important for the successful adoption of CASE technology. The data for the study were collected through a field survey of IS managers in the midwest area and 90 responses were received. The results of discriminant ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
61
3

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(79 citation statements)
references
References 36 publications
(55 reference statements)
6
61
3
Order By: Relevance
“…The research results concerning the implementation of innovations [13] and IT innovations [25] are consistent with the above findings of Rogers.…”
Section: Characteristics Of An Innovationsupporting
confidence: 87%
“…The research results concerning the implementation of innovations [13] and IT innovations [25] are consistent with the above findings of Rogers.…”
Section: Characteristics Of An Innovationsupporting
confidence: 87%
“…The reason is that these initiatives are mostly addressing the project level. The introduction of a tool as an SPI initiative can however have farreaching consequences, that is for the project [42], [134], but also both for the product quality [57], [63], [66], [73] and the organization [55], [72], [83], [96].…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…They are able to change the existing work culture and their attitude will influence the acceptance of BIM among the staff. Gilligan & Kunz [29] and Premkumar & Potter [30] revealed that top management support has been recognised as an important variable in technology implementation studies and commitment from them is the major success factor for adopting BIM technology. From the interview, it was found that organisations that have significant support from the top management are able to use BIM in their construction projects.…”
Section: Fig-3: Bim Implementation Team Structure For Cbmentioning
confidence: 99%